Photodissociation dynamics of methyl iodide probed using femtosecond extreme ultraviolet photoelectron spectroscopy. Issue 44 (4th November 2020) - Warne, Emily M.; Downes-Ward, Briony; Woodhouse, Joanne; Parkes, Michael A.; Springate, Emma; Pearcy, Philip A. J.; Zhang, Yu; Karras, Gabriel; Wyatt, Adam S.; Chapman, Richard T.; Minns, Russell S.
Abstract : Femtosecond pump–probe photoelectron spectroscopy measurements using an extreme ultraviolet probe have been made on the photodissociation dynamics of UV (269 nm) excited CH3 I. Abstract : Femtosecond pump–probe photoelectron spectroscopy measurements using an extreme ultraviolet probe have been made on the photodissociation dynamics of UV (269 nm) excited CH3 I. The UV excitation leads to population of the 3 Q0 state which rapidly dissociates. The dissociation is manifested as shifts in the measured photoelectron kinetic energy that map the extending C–I bond. The increased energy available in the XUV probe relative to a UV probe means the dynamics are followed over the chemically important region as far as C–I bond lengths of approximately 4 Å.